A Prototype Study Evaluating the Linguistic Proficiency of Year 1 ELTE Students at Eastern Mediterranean University, North Cyprus. (1st January 2016) - Osam, Necdet; Korun, Gulsun
Abstract: With English being the lingua franca and the most commonly taught foreign language worldwide, many institutions such as the Eastern Mediterranean University in Northern Cyprus have adopted the English language as the medium of instruction in order to meet social and educational needs. Yet, although the final year students of the mentioned university are regarded to have acquired proficiency in English, the teaching staff are purporting that the first year courses are, in fact, language learning sessions for students whose language competency even at the end of their four-year undergraduate studies continues to be debatable. Based on this controversy, this case study aims to determine whether the English language development of the EMU-ELTE year 1 students meets/ satisfies certain predetermined educational and social requirements. This longitudinal study involves the continuous normative evaluation of students' language abilities through English.